DUKUNGAN SUAMI DAN KELUARGA DALAM UPAYA PENCEGAHAN POST PARTUM BLUES - Yuwanti; Miftahul Fadhilah Azzahra (LPPM AN Nuur, 2025)
Background: Pregnancy, childbirth, and the postpartum period are critical times for women, as they undergo various physiological and psychological adaptations that result in both physical and emotional changes. These adaptations require support from partners or family members to ensure a smooth transition and to prevent potential issues and complications, one of which is postpartum blues. Objective: To provide knowledge and increase the involvement of husbands and families in preventing postpartum blues. Method: This community service was conducted by providing educational counseling sessions to respondents together with their husbands or family members. Results: Community service through counseling sessions was able to enhance the support of husbands and families in preventing postpartum blues. Conclusion: Support from husbands and families during the adaptation process of pregnancy, childbirth, and postpartum can help prevent the occurrence of postpartum blues.